Kolaborasi Pemerintah Desa dan Komunitas dalam Pengembangan Kampung Nusantara di Desa Cintakarya Kecamatan Parigi Kabupaten Pangandaran - Hilya Auliya; Dini Yuliani; Regi Refian Garis (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study focuses on the importance of synergy between village government and communities in supporting local potential-based development. Kampung Nusantara, an innovative program in Cintakarya Village, Parigi District, Pangandaran Regency, requires solid cooperation between the village government and the community for effective and sustainable village development. However, in practice, collaboration between the two parties has not been optimal. The main problem identified in this study is the lack of coordination between the village government and the community. This is due to the absence of regulations that clearly define the roles of each party and the limited capacity of existing human resources. As a result, the existing collaboration has not been systematic and has not fully supported the achievement of Kampung Nusantara's development goals. The method used in this study is a qualitative descriptive approach with a case study approach in Cintakarya Village. The findings of this study indicate that despite several obstacles, there are still positive efforts to improve collaboration between the village government and the community. Some of these efforts include the establishment of a joint communication forum, capacity building training, and program support from external partner institutions that play a role in supporting village development. This study recommends several steps to improve this collaboration, including increasing communication between the village government and the community, clarifying the roles and responsibilities of each party, and strengthening village institutions. This is expected to foster more effective collaboration, which in turn will support the achievement of sustainable development goals in Kampung Nusantara, Cintakarya Village. Furthermore, this study emphasizes the importance of strengthening human resource capacity at both the village government and community levels.